Dinner ladies don't count - Ashley Bernard; Duchesne Janet (London ; New York : Julia MacRae Books, 1981)
When Donna's birthday cards disappear, Jason gets blamed. How can he prove his innocence or explain why he did all those other naughty things in school that morning?